Evidence of reassortment of pandemic H1N1 influenza virus in swine in Argentina: are we facing the expansion of potential epicenters of influenza emergence? - Pereda, Ariel (2011)
In this report, we describe the occurrence of two novel swine influenza viruses (SIVs) in pigs in Argentina. These viruses are the result of two independent reassortment events between the H1N1 pandemic influenza virus (H1N1pdm) and human-like SIVs, showing the constant evolution of influenza viruses at the human–swine interface and the potential health risk of H1N1pdm as it appears to be maintained in the swine population. It must be noted that because of the lack of information regarding the circulation of SIVs in South America, we cannot discard the possibility that ancestors of the H1N1pdm or other SIVs have been present in this part of the world. More importantly, these findings suggest an ever-expanding geographic range of potential epicenters of influenza emergence with public health risks.